1993
DOI: 10.1037/0022-3514.65.3.494
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of marital interaction among Black and White newlyweds.

Abstract: Perceptions of marital interactions were gathered from a representative sample of urban newlywed couples (199 Black and 174 White). A factor analysis of the reports found 6 factors common to husbands and wives: Disclosing Communication, Affective Affirmation, Negative Sexual Interaction, Traditional Role Regulation, Destructive Conflict, and Constructive Conflict. Avoiding Conflict was specific to men and Positive Coorientation was specific to women. Wives reported fewer constructive and more destructive confl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(56 citation statements)
references
References 70 publications
4
51
0
1
Order By: Relevance
“…Using this particular experimental design (orientation by initiator), we were able to determine, from an examination of the uninfluenced steady states that in homosexual relationships the initiator of the Gottman et al 83 conflict started positively, while in heterosexual relationships the initiator started negatively. Other research suggests that women presenting conflict issues to men is the most common pattern in heterosexual couples (Ball, Cowan, & Cowan, 1995;Oggins, Veroff, & Leber, 1993). This gender pattern fits with the well-known female demand-male withdraw pattern identified by Christensen and colleagues (e.g., Christensen and Heavey, 1990).…”
Section: Discussionsupporting
confidence: 52%
“…Using this particular experimental design (orientation by initiator), we were able to determine, from an examination of the uninfluenced steady states that in homosexual relationships the initiator of the Gottman et al 83 conflict started positively, while in heterosexual relationships the initiator started negatively. Other research suggests that women presenting conflict issues to men is the most common pattern in heterosexual couples (Ball, Cowan, & Cowan, 1995;Oggins, Veroff, & Leber, 1993). This gender pattern fits with the well-known female demand-male withdraw pattern identified by Christensen and colleagues (e.g., Christensen and Heavey, 1990).…”
Section: Discussionsupporting
confidence: 52%
“…For instance, within Black-White couples, Oggins et al (1993) found that Black spouses are more likely than White spouses to leave a conflict to calm down. Conversely, Crohan (1996) found that White parents use withdrawal patterns to deal with conflict, particularly after the birth of a child.…”
Section: Person Characteristics and Conflictmentioning
confidence: 96%
“…In a decade review of research on African American families, McLoyd and colleagues concluded that current evidence, although limited, does not support fundamental differences in the predictors of marital satisfaction and stability for African American versus European American couples (McLoyd, Cauce, Takeuchi, & Wilson, 2000). A few distinctive characteristics of African American marriages have been identified, including high egalitarianism (Hunter & Sellars, 1998;Kane, 1992;Orbuch & Eyster, 1997), involvement with extended family (McAdoo, 1981), and mutual self-disclosure (Oggins, Veroff, & Leber, 1993).…”
mentioning
confidence: 99%